Strengthening Posyandu Cadres through an Oketani Massage E-Booklet to Support Exclusive Breastfeeding - Anna Waris Nainggolan; Dessy Ratna Sari Sembiring; Imarina Tarigan; Sodiria Zega; Putri Amanda Sari (Room of Civil Society Development, 2026)
Exclusive breastfeeding remains an important public health strategy to support infant growth and development during the first 1,000 days of life. In Dusun VIII, Bangun Rejo Village, Deli Serdang Regency, exclusive breastfeeding coverage is estimated at 65–70%, which is still below the national target of 80%. Several contributing factors include limited breastfeeding management skills, mothers’ perception of insufficient milk production, limited family support, and the lack of standardized educational media for Posyandu cadres. This community service programme aimed to strengthen the role of Posyandu/PKK cadres in supporting breastfeeding mothers through education, practical introduction to Oketani Massage, and the use of an Oketani Massage E-Booklet as digital educational media. The programme was implemented in Bangun Rejo Village from 20 February to 25 March 2026 using a participatory and descriptive community empowerment approach. The activities included socialization, exclusive breastfeeding literacy education, Oketani Massage simulation using a breast phantom, distribution of the E-Booklet, and descriptive evaluation through attendance records, activity documentation, observation, and informal feedback from cadre representatives. A total of 15 Posyandu/PKK cadres participated in the activity. The programme produced an Oketani Massage E-Booklet and received positive responses from cadres, particularly regarding its usefulness as a practical reference that can be accessed repeatedly through mobile phones. This programme contributes to community-based breastfeeding support by providing cadres with basic lactation education, practical simulation experience, and reusable digital learning material.